The photocatalytic hydrogen evolution enhancement of the MoS2 lamellas modified g-C3N4/SrTiO3 core-shell heterojunction. (December 2020) - Pan, Jiaqi; Liu, Yanyan; Ou, Wei; Li, Shi; Li, Hongli; Wang, Jingjing; Song, Changsheng; Zheng, Yingying; Li, Chaorong
Abstract: The MoS2 lamellas modified g-C3 N4 /SrTiO3 core-shell heterojunction is prepared via a simple continuous hydrothermal-annealing method. There, the g-C3 N4 shell is deposited on the surface of as-prepared SrTiO3 nanosphere, and then the MoS2 lamellas grow on the surface of core-shell heterojunction. Evaluated by the hydrogen evolution, the as-prepared MoS2 /g-C3 N4 /SrTiO3 core-shell heterojunction exhibits an obvious photocatalytic enhancement of about ∼30 folds than single SrTiO3 nanospheres, which can be mainly ascribed to that, the core-shell heterojunction can promote the charge carriers separation efficiently and the Pt-like behavior MoS2 can promote the photo-generated electrons diffusing into water quickly. Additionally, the ultrathin MoS2 lamellas with a mass of edge S atoms can provide sufficient HER active sites and shorten photoelectron transport route to improve photocatalytic stability. Graphical abstract: Image 1 Highlights: Pt-like behavior MoS2 can capture/diffuse photo-electron into water quickly . Core-shell heterojunction can excit/separate photo-generated carriers efficiently. Ultrathin lamellas can shorten transfer route to promote photo-electron diffusing. MoS2 lamellas can provide sufficient HER active sites.